Drought and Property Prices: Empirical Evidence from Provinces of Iran - Mohammad Reza Farzanegan; Mehdi Feizi; Hassan F. Gholipour (Economics of Disasters and Climate Change, 2020)
This study examines the effect of drought on housing and residential land prices in Iran. Using panel data covering the 2006–2015 period for 31 provinces of Iran and applying a dynamic system and the difference Generalized Methods of Moments (GMM) methods, we find that an increase in the balance of water (reducing the severity of drought) within provinces has a positive effect on property prices. Our results are robust, controlling for province fixed effects, time trend, and a set of control variables that may affect property prices.
Keywords: R21; R31; Q54; 330; Drought; Property prices; Residential land; Housing; Iran